Interleukin-23 Inhibitors - Esra Adışen (Galenos Publishing House, 2022)
For adult patients with moderate to severe plaque psoriasis scheduled for systemic therapy, FDA-approved agents that act via interleukin-23 (IL-23) inhibition are guselkumab, tildrakizumab, and risankizumab. Response to treatment should be evaluated after a 12-week treatment period in psoriasis patients being treated with IL-23 inhibitors. In patients with partial response, dose increase may be planned, or topical corticosteroids, vitamin D analogs, methotrexate, or phototherapy (UVB) may be added to the treatment.